Inter-organisational governance in megaprojects: a systematic review and an agenda for future research - Pathak, Raj; Turner, Neil; Alinaghian, Leila (British Academy of Management, 2023)
The review analysed 4,536 titles. 781 papers were selected for the title and abstract review after applying exclusion criteria and 81 papers were identified for the full review. Gioia method was applied to extract the first-order and second-order concepts and aggregate dimensions. The thematic analysis illustrates that megaprojects are delivered through multi-party settings and the governance is regarded as dynamic, processual and anchored in multiple levels. Megaproject governance mechanisms include informal and informal approaches. Committed leadership, collaboration, stakeholder management and culture are key components to enable the governance mechanisms. The main challenges in the implementation of a complex infrastructure project are not technical but are rather those related to how to govern the work in a complex inter-organisational setting that brings together a diverse set of actors who differ in their values, culture and goals.